2014
DOI: 10.3791/50941
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Stimulatory Device for Evoking Point-like Tactile Stimuli: A Searchlight for LFP to Spike Transitions

Abstract: Current neurophysiological research has the aim to develop methodologies to investigate the signal route from neuron to neuron, namely in the transitions from spikes to Local Field Potentials (LFPs) and from LFPs to spikes.LFPs have a complex dependence on spike activity and their relation is still poorly understood 1 . The elucidation of these signal relations would be helpful both for clinical diagnostics (e.g. stimulation paradigms for Deep Brain Stimulation) and for a deeper comprehension of neural coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…In our experiments, epicortical stimuli, although disturbing parallel natural sensory stimuli, once discontinued, did not show any extra interference with the responses to those stimuli. The natural stimuli were very light threshold sensory touches, repeatedly presented on single fingertips by a device delivering less than one millisecond-long inputs over some 1 mm 2 (Zippo et al, 2014 ). They were apt to elicit extremely evident responses on a significant cluster of recording electrodes with evident stereotactical distribution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our experiments, epicortical stimuli, although disturbing parallel natural sensory stimuli, once discontinued, did not show any extra interference with the responses to those stimuli. The natural stimuli were very light threshold sensory touches, repeatedly presented on single fingertips by a device delivering less than one millisecond-long inputs over some 1 mm 2 (Zippo et al, 2014 ). They were apt to elicit extremely evident responses on a significant cluster of recording electrodes with evident stereotactical distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In detail, in Figures 2A,B the electrical scheme and the controller with optic insulator for the electrical grid stimulus control are respectively displayed. In Figure 2C the home-made device able to release point-like (1 mm 2 ) sub-millisecond random stimuli (see Zippo et al, 2014 ) are shown. Figure 2D : The overall 16 channel impedance profiles during the implantation period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The motor patterns were checked by a walking motor scheme test that shows the postural rhythms and patterns of paw placing during walking. Specifically, mechanical allodynia has been measured by stimulating with Von Frey filaments 16 the plantar aspect of the treated paw (well accessible after placing the rat over a metal grid). Measures of paw withdraw latencies were then collected for all the rats every other day with double or triple tests in short time (5 minutes) intervals.…”
Section: Methodsmentioning
confidence: 99%